Study of Inter-arm Variation of Blood Pressure in Normal and Diabetic Individual in Out Patient Department of Nepal Medical College - Poudyel, Pragati; Adhikar, Seerina (Annapurna Journal of Health Sciences, 2023)
Introduction: Growing incidence of hypertension and its significant association with diabetes mellitus are being observed in both developing and developed countries around globe. Scanty literature is available about the comparative study of inter-arm variation of blood pressure in normal individuals and diabetic among Nepalese population. This research was performed to determine extent of inter-arm variation in normal individuals and diabetics.Methods: A descriptive observational study was carried out from 2013 January to 2014 January in a tertiary level teaching hospital of Nepal. After taking the consent and giving necessary instructions, blood pressures were measured in both the arms one after another in sitting posture using mercurial sphygmomanometer and Littman cardiosonic stethoscope. Arterial blood pressure was measured by palpatory method followed by auscultatory method The cuff pressure at which the tap sound were first perceived was noted as systolic blood pressure (SBP). Similarly, diastolic blood pressure (DBP) was noted at the point where the sound disappeared.Results: A total of 120 volunteers between ages of 40-80 years were studied. Highly significant inter-arm variation of both SBP and DBP was found in diabetics as compared to normal (p